2018
DOI: 10.1177/0361198118797215
|View full text |Cite
|
Sign up to set email alerts
|

Sensors and the City: Urban Challenges for Parking Occupancy Detection and Pricing

Abstract: Implementing performance parking using demand-driven hourly parking meter rates and real-time occupancy information improves the customer experience and provides more available on-street parking in selected cities across the United States. The implementation of performance parking is not necessarily simple, however, and planners must overcome a host of challenges posed by the urban environment. This paper discusses an approach with the potential to become the state-of-the-practice for developing real-time avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A study by District Department of Transportation (DDOT) identified a range of data collection technologies including GPSenabled cameras, time-lapse cameras, license plate recognition devices, and in-ground sensors (16). Through a series of pilot projects and academic evaluations, the same group of researchers uncovered several limitations to existing parking sensor technology, including prohibitive cost and a considerable number of false positives (17). They also applied predictive modeling to strategically deploy parking assets where they were most needed (18).…”
mentioning
confidence: 99%
“…A study by District Department of Transportation (DDOT) identified a range of data collection technologies including GPSenabled cameras, time-lapse cameras, license plate recognition devices, and in-ground sensors (16). Through a series of pilot projects and academic evaluations, the same group of researchers uncovered several limitations to existing parking sensor technology, including prohibitive cost and a considerable number of false positives (17). They also applied predictive modeling to strategically deploy parking assets where they were most needed (18).…”
mentioning
confidence: 99%
“…SFPark piloted one of the first large-scale deployments of real-time monitoring of on-street parking with 8,200 in-ground magnetometer sensors [16]. While the results from SFPark and similar deployments of in-ground sensors (with an average accuracy-availability of 85%) have been promising [3], [17], the installation and maintenance costs of these sensors are usually high [8], [18].…”
Section: B Bay Occupancy Data Collectionmentioning
confidence: 99%
“…Effective parking management, however, relies on reliable and integrated occupancy-payment data at the bay-level [1], [22]. Such data enable city planners and local governments to implement performance-based parking pricing and parking availability forecasting tools, which in turn help improve traffic flow and overall user experience [17], [23]. Furthermore, patterns of on-street parking demand can more accurately be investigated, relying on integrated occupancy-payment data.…”
Section: Other On-street Parking Datamentioning
confidence: 99%
“…Substantial research examines parking in urban cities, national parks, and public lands by consideration of various factors impacting transportation planning, urban challenges for parking occupancy detection, overall parking assessment, the role played by social norms, communication responsibility, and institutional environment in regulating parking behaviour and the social impacts of shared transportation [5,7,[18][19][20][21][22][23][24]. Those factors impacting the availability of parking include (i) possible closure of existing kerbside parking due to new public transport infrastructure such as light rails, (ii) increasing demand due to population growth, (iii) increasing freight and servicing activities, (iv) changes to other parking facilities (e.g., closure of existing carparks for developing new residential and commercial buildings), (v) real-time availability for on-street parking in an urban environment, and (vi) the impact of a sharp increase in construction volume (activity) and the development zone's compaction [25].…”
Section: Introductionmentioning
confidence: 99%